Adaptive calibration for reduced fuel consumption and emissions. (December 2016) - Guardiola, Carlos; Pla, Benjamín; Bares, Pau; Waschl, Harald
This paper presents a model-based approach for continuously adapting an engine calibration to the traffic and changing pollutant emission limits. The proposed strategy does not need additional experimental tests beyond those required by the traditional calibration approach. The method utilises information currently available in the engine control unit to adapt the engine control to the particular driving patterns of a given driver. Additional information about the emissions limits should be provided by an external structure if an adaptation to the pollutant immission is required. The proposed strategy has been implemented in a light-duty diesel engine, and showed a good potential to keep NO x emissions around a defined limit.